2016
DOI: 10.1088/0268-1242/31/10/105005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced resistive switching performance for bilayer HfO2/TiO2resistive random access memory

Abstract: We prepared bilayer HfO 2 /TiO 2 resistive random accessory memory (RRAM) using magnetron sputtering on an ITO/PEN flexible substrate. The switching voltages (V SET and V RESET ) were smaller for the Pt/HfO 2 /TiO 2 /ITO device than for a Pt/HfO 2 /ITO memory device. The insertion of a TiO 2 layer in the switching layer was inferred to act as an oxygen reservoir to reduce the switching voltages. In addition, greatly improved uniformity was achieved, which showed the coefficient of the variations of V SET and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…[9] Figure 1a shows typical I-V curves of ITO/TiO 2 /HfO 2 /Pt device. [18] The detail RS mechanisms related to the movements of oxygen vacancies will be discussed below. The device shows stable bipolar RS behavior.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Figure 1a shows typical I-V curves of ITO/TiO 2 /HfO 2 /Pt device. [18] The detail RS mechanisms related to the movements of oxygen vacancies will be discussed below. The device shows stable bipolar RS behavior.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that the electrons have to surpass an additional potential energy barrier between the conductive lament (CF) and the N:ITO electrode. 23,24 According to the current tting results, we further investigated the RS mechanisms for both devices to explore the possible reason for the performance improvement in the memory cell with the ITO transparent electrode induced by SCFnitridation treatment. During the repeated set and reset process, the formation and rupture of CFs were accompanied by the recombination and separation of oxygen ions (O 2À ) and oxygen vacancies (Vo + ) near by the ITO electrode.…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33] In our previous work, it is observed that operating voltage of Pt/HfO 2 /TiO 2 /ITO RRAM device is lower than that of Pt/HfO 2 /ITO RRAM device. [34] Following our previous work, we proposed bilayered HfO 2 /TiO x cognitive memristor. The neuromorphic device can operate at low voltage as low as 0.6 V. Multistore memory model of brain is demonstrated.…”
Section: Introductionmentioning
confidence: 99%